Konstruksi Dokumentasi Alahan Nagari Paninggahan - Erick Immanuel; Lilian Lilian; Muhammad Rizki (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines the documentation process of Alahan Muaro Paninggahan, an economic and cultural tradition in Nagari Paninggahan, Solok Regency, West Sumatra. The alahan system is a form of natural resource management passed down through generations and serves as a social, economic, and cultural identity platform for the local community. In a modern context, this research highlights how digital technology is beginning to be utilized to document, promote, and preserve the alahan tradition through social media, visual content, and other digital platforms. The research method used was descriptive qualitative, with data collection techniques including field observation, in-depth interviews, and photo and video documentation. The results indicate that digitalization plays a significant role in introducing local cultural values to a wider audience and increasing public awareness of the potential of a tradition-based economy. In addition to preserving culture, digitalization is also an effective strategy for supporting tourism promotion and strengthening regional identity.